Evolution of Budget Expenditures and Budget Investment in the Context of Structural Transformation of the National Economy of Ukraine - Ivanchenkov Viacheslav S. (Problemi Ekonomiki)
The article is dedicated to the study of the evolution of budget expenditures and budget investments in Ukraine in the context of the structural transformation of the national economy. The article substantiates the directions for improving the efficiency of budget policy to ensure sustainable economic growth in Ukraine. The importance of using various methods and forms of the budget mechanism is revealed, among which budgetary levers play a key role. It is determined that the main instruments of the State influence on economic processes are revenues, taxes, interbudgetary transfers, grants, subsidies, and government loans. The significance of the State budget as an effective tool of budget policy capable of ensuring economic growth, reducing unemployment, and improving social standards is disclosed. The dynamics of State expenditure indicators in the structure of Ukraine’s GDP for the years 2019–2023 are analyzed. It is substantiated that the significant increase in expenditures in 2022–2023 is due to the necessity of financing defense needs under martial law conditions. A conclusion has been drawn regarding the impact of budgetary levers on stimulating economic activity, creating jobs, and ensuring sustainable development. It has been shown that government spending on infrastructure projects, education, and healthcare serves as important factors for increasing labor productivity and improving the welfare of the population. It is determined that, under conditions of armed aggression, priority remains on financing the military-industrial complex, social programs, and supporting vulnerable segments of the population. The features of budgetary investment as an effective tool for economic development, taking into account modern challenges and threats, have been revealed. It is found that Ukraine’s public capital expenditures in 2022 significantly decreased; however, in 2023, there is a trend of their growth, which is explained by the need to restore the destroyed infrastructure. Attention has been drawn to the importance of ensuring transparency and accountability in the field of budgetary investment to achieve the strategic goals of sustainable development.